Produksi Biomassa dan Minyak Atsiri Kemangi (Ocimum basilicum L.) pada Berbagai Dosis Pupuk Nitrogen dan Pupuk Cair Hayati - Juang G. Kartika; Ketty Suketi; Nilam Mayasari (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2016)
ABSTRACTBasil (Ocimum basilicum L.) is one of essential oil producers. Essential oil price fluctuates, one of the reasons is because of inappropriate cultivation which vary the supply. The research was conducted to determine the best rate of nitrogen fertilizer and the effect of biological liquid fertilizer on the essential oil production of basil. The experiment was arranged in Randomized Complete Block Design with two factors. The first factor was three levels of nitrogen rate: 0, 22.5, and 45 kg ha-1 and the second factor was two levels of biological liquid fertilizer rate; 0 and 2 L ha-1 for three replications of each treatment. Nitrogen increased the number of branches, flowers, and leaf length variables. Nitrogen rate of 22.5 kg ha-1 gave a higher economic value on the basil of essential oil production. Biological liquid fertilizer increased the height and number of basil leaves variables, but it was not impacted the yield and essential oil of basil.Keywords: branches, distillation, fertilization, yieldABSTRAKKemangi (Ocimum basilicum L.) merupakan salah satu sumber penghasil minyak atsiri. Harga minyak atsiri yang fluktuatif, salah satunya disebabkan budidaya yang belum tepat. Penelitian ini bertujuan untuk mendapatkan dosis pupuk nitrogen terbaik dan mempelajari pengaruh pupuk cair hayati terhadap produksi minyak atsiri pada tanaman kemangi. Percobaan penelitian disusun dalam Rancangan Kelompok Lengkap Teracak terdiri dari dua faktor yaitu faktor pertama perlakuan dosis nitrogen 3 taraf; 0, 22.5, dan 45 kg ha-1 dan faktor kedua perlakuan dosis pupuk cair hayati 2 taraf; 0 dan 2 L ha-1 dalam 3 ulangan masing-masing perlakuan. Secara tunggal nitrogen meningkatkan peubah jumlah cabang sekunder, jumlah bunga dan panjang daun. Nitrogen dengan dosis 22.5 kg ha-1 memiliki nilai ekonomi lebih tinggi pada produksi minyak atsiri kemangi. Pengaruh pupuk cair hayati meningkatkan peubah tinggi dan jumlah daun kemangi. Pupuk cair hayati tidak mempengaruhi rendemen dan produksi minyak atsiri kemangi.Kata kunci: bobot, destilasi, pemupukan, rendemen